Cellular Mechanisms of Multiple Myeloma Bone Disease. (29th May 2013) - Oranger, Angela; Carbone, Claudia; Izzo, Maddalena; Grano, Maria
Abstract : Multiple myeloma (MM) is a hematologic malignancy of differentiated plasma cells that accumulates and proliferates in the bone marrow. MM patients often develop bone disease that results in severe bone pain, osteolytic lesions, and pathologic fractures. These skeletal complications have not only a negative impact on quality of life but also a possible effect in overall survival. MM osteolytic bone lesions arise from the altered bone remodeling due to both increased osteoclast activation and decreased osteoblast differentiation. A dysregulated production of numerous cytokines that can contribute to the uncoupling of bone cell activity is well documented in the bone marrow microenvironment of MM patients. These molecules are produced not only by malignant plasma cells, that directly contribute to MM bone disease, but also by bone, immune, and stromal cells interacting with each other in the bone microenvironment. This review focuses on the current knowledge of MM bone disease biology, with particular regard on the role of bone and immune cells in producing cytokines critical for malignant plasma cell proliferation as well as in osteolysis development. Therefore, the understanding of MM pathogenesis could be useful to the discovery of novel agents that will be able to both restore bone remodelling and reduce tumor burden.